WELFARE ANALYSIS OF FRESH FISH TRADERS IN DELITUA TRADITIONAL MARKET, DELITUA DISTRICT, DELI SERDANG REGENCY - Saurina Septiani Sitanggang; Nina Novira (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2022)
This study aims to determine: (1) How is the welfare level of the fish traders in the Delitua Traditional Market in terms of their material conditions? (2) How is the welfare level of the fish traders in the Delitua Traditional Market seen from their spiritual condition? (3) How is the welfare level of the fish traders at the Delitua Traditional Market in terms of their social conditions? This research was conducted at the Delitua Traditional Market, Delitua District, Deli Serdang Regency, North Sumatra with a total population of 20 people, who also became the sample in this study (Total Sampling). Data collection techniques were carried out through direct observation and questionnaires. The data analysis technique used is descriptive qualitative analysis. The results of the research show that: Traders' Welfare Level can be measured based on their material condition, social condition, and spiritual condition. Merchants' Welfare can be classified into 3 Criteria, namely High Welfare, Medium Welfare, and Low Welfare. Based on the research that has been done, it can be seen that the welfare level of fresh fish traders in the Delitua Traditional Market is mostly in the moderate level of welfare criteria. Where from 20 respondents, there are 6 respondents who have a high level of welfare, as many as 11 respondents have a moderate level of welfare, and 3 respondents have a low level of welfare.